2019
DOI: 10.3390/molecules24213920
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Hepatotoxic Components in Fructus Gardeniae and Their Effects on Rat Liver BRL-3A Cells

Abstract: Fructus Gardeniae (FG) is a common Chinese medicine and food. However, the toxicity of FG has drawn increasing concern, especially its hepatotoxicity. The purpose of this study was to screen the hepatotoxic components of FG and evaluate their effects on rat liver BRL-3A cells. The chemical composition of FG was determined by HPLC-ESI-MS. CCK-8 assay was used to evaluate the cytotoxicity of ten chemical components from FG, and then the toxic components with significant inhibitory activity were selected for furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…However, it should be noted that a major GF ingredient, geniposide, has been shown to be acutely hepatotoxic at high doses [23,24]. Possible toxicity of other GF ingredients has also been suggested [25]. In this study, pathological changes such as calcification and fibrosis of the mesenteric vein in the colon were not observed.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, it should be noted that a major GF ingredient, geniposide, has been shown to be acutely hepatotoxic at high doses [23,24]. Possible toxicity of other GF ingredients has also been suggested [25]. In this study, pathological changes such as calcification and fibrosis of the mesenteric vein in the colon were not observed.…”
Section: Discussionmentioning
confidence: 51%
“…Various pharmacological effects of crocin and crocetin, as well as toxicity, have been reported [31,32]. Pharmacological activity has also been suggested for other GF ingredients, and in vitro studies suggest that many of them may have cytotoxic/hepatotoxic effects [25]. erefore, investigation of GF ingredients and the mechanisms responsible for the pathogenesis of MP warrant further extensive studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research groups have explored the binding of geniposide and genipin to tumor necrosis factor receptor 1 (TNFR1), an upstream protein of NF‐κB, and mitogen‐activated protein kinase (MAPK) and found that FG constituents can activate related inflammatory pathways (Li et al., 2019). We verified that the expressions of NF‐κBp65, COX‐2, and iNOS in the liver and kidney increase to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines play a major role during the process of liver inflammation, especially from steatosis to steatohepatitis, or from inflammatory infiltration to liver injury [31]. Previous studies reported that carbohydrates, therapeutic drugs and the hypoxia/reoxygenation model could increase the levels of IL-1 β and IL-6 in the supernatant of BRL-3A cells [13,32,33]. Inflammation interferes with the expression of genes related to lipid metabolism, leading to lipid accumulation [32].…”
Section: Discussionmentioning
confidence: 99%